Graph-analytical analysis of prediction of mechanical properties of welded joints of steel system Fe-Cr-Ni-Si - Попов, Сергей Николаевич (Eastern-European Journal of Enterprise Technologies, 2013)
The article discusses the possibility of using the graph-analytical method for the analysis of prediction of the mechanical properties of the welded joints of heat-resistant steels Fe-Cr-Ni-Si. The heat-resistant steels and alloys, used for the manufacture of parts, which operate at high temperatures under a hard-intense state for a specified period of time, should withstand the tension, causing the deformation that does not lead to destruction. The aim of the work is to optimize the chemical composition of the welded heat-resistant metal for fittings of thermic furnaces, to find the material with maximum performance characteristics, and to study the distribution of the mechanical properties (HV hardness) on section of welded joint and heat-affected zone from heat-resistant austenitic and austenitic-ferritic steels. Theoretically we have proved the possibility of correction of the defects of fittings of thermic furnaces by welding methods. We have held the graphic-analytical analysis of mathematical models in the form of regression equations, describing the joint influence of the alloying elements (C, Cr, Ni) and temperature gradient (T) on the physical and mechanical properties (HV hardness) of the heat-resistant steels and alloys. The optimal values for the content of the alloying elements were determined; they can provide the optimal values of the physical and mechanical properties of the welded metal: C = 0,14-0,19%, Cr = 21-23%, Ni = 17-19%.